Upaya Meningkatkan Aktivitas Dan Hasil Belajar IPA Pada Materi Sistem Tata Surya Melalui Model Kooperatif Tipe Group Investigation (GI) Siswa Kelas VI MIN 1 Kota Lhokseumawe - Zuhra, Fathimah (Jurnal Cakrawala, 2023)
The purpose of this study is to improve the activity and learning outcomes of science on the Solar System material. The learning model used in this study is a Group Investigation (GI) type cooperative model. The subjects of this study were class VI MIN 1 students in Lhokseumawe City, totaling 32 students consisting of 14 male students and 18 female students. This research was carried out in the 2019/2020 academic year within a period of 3 months, namely from September 2019 to November 2019 in odd semesters. The methodology of this study is Classroom Action Research (PTK) consists of two cycles and each cycle consists of two meetings. Each cycle consists of planning, execution, observation and reflection. The data collection technique is to collect test scores that are carried out at the end of each learning in each cycle using a question instrument (written test). Observation data is carried out by looking at student activity in the learning process. The data are analyzed by means of percentage statistics. The results showed that there was an increase in student learning activities in both cycles, from the enough to the good category to the good category to the very good. The completion of student learning outcomes increased from 37.50% in the pre-cycle to 62.50% in cycle I and increased to 87.50% in cycle II. The application of the Group Investigation (GI) type cooperative model can improve science learning activities and outcomes in the Solar System material for class VI MIN 1 students in Lhokseumawe City for the 2019/2020 Academic Year.